Pengaruh Diameter Pasir Silika Dan Zeolit Pada Saringan Pasir Lambat Dalam Menurunkan Parameter Kekeruhan Air Sungai Siak - Denisa Nurmalia; Shinta Elystia; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The need for clean water is needed by various groups of people. People who live on the banks of the Siak River in Limbungan Village, Rumbai Pesisir Sub-District use Siak River water for clean water of bathing, washing and latrines by used it directly. Siak River water used by residents has several parameters that exceed the quality standard so that the use of river water must be processed first. One simple system that can process Siak River water is a slow sand filter with the addition of zeolite. The purpose of this study was to determine the efficiency of decreasing turbidity parameters by slow sand filters. In this study variations in the diameter of silica sand – zeolite (0,15 – 0,35) mm, diameter of silica sand – zeolite (0,35 – 0,55) mm and variations in flow rate filtration on slow sand filters (0,1 ; 0,2 and 0,3) m/hour. Based on the results of the study, the highest removal efficiency was found in slow sand filter reactors with media diameters (0,15 – 0,55) mm and with flow velocities of 0,1 m / hour, removal of turbidity is 97,08%Keywords: Slow Sand Filter, Silica Sand, Zeolite, Siak River Water